Explaining and Forecasting Inflation in Turkey - Domaç, Ilker (World Bank, Washington, D.C., 2013)
The growing adoption of an inflation targeting framework in emerging market economies has increased the importance of understanding inflation dynamics and forecasting its future path in these countries. The author considers the case of Turkey and investigates the performance of models that have some theoretical foundations. To this end, his study focuses on mark-up models, monetary models, and the Phillips curve. The findings suggest that the mark-up models have the best in-sample performance followed by money gap models and the Phillips curve. The empirical results from out-of-sample forecasting performance for the period covering the new economic program (May 2001-December 2002), however, show that the Phillips curve and the money gap models perform better than mark-up models. These findings, in turn, imply that (1) Phillips curves augmented with the exchange rate and money models might provide complementary views in the Turkish context; and (2) the relative importance of output gap and monetary disequilibrium in the inflation process has increased under the floating exchange rate regime. The results underscore the importance of relying on multiple models of inflation in the conduct of Turkish monetary policy.